1958
DOI: 10.1021/j150559a019
|View full text |Cite
|
Sign up to set email alerts
|

The System Zirconium–Nickel and Hydrogen

Abstract: The interaction of the intermetallic compound ZrNi with hydrogen was studied, and pressure-composition isotherms were obtained at 100, 200 and 250°. There was no resemblance to the zirconium-hydrogen system. The alloy formed a definite hydride at a limiting composition ZrNiHa, and possibly a second hydride at ZrNiH. X-Ray and density measurements on both the alloy and the hydrides indicated a distorted cubic structure for all phases. Hysteresis was observed on the isotherms and a possible explanation for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1962
1962
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(55 citation statements)
references
References 0 publications
1
52
0
1
Order By: Relevance
“…Thus, they are not useful for reversible hydrogen storage if only the pure binary hydrides are considered ). Libowitz et al (Libowitz et al, 1958) could achieve a breakthrough in the development of hydrogen storage materials by discovering the class of reversible intermetallic hydrides. In 1958 they discovered that the intermetallic compound ZrNi reacts reversibly with gaseous hydrogen to form the ternary hydride ZrNiH 3 .…”
Section: Conventional Metal Hydridesmentioning
confidence: 99%
“…Thus, they are not useful for reversible hydrogen storage if only the pure binary hydrides are considered ). Libowitz et al (Libowitz et al, 1958) could achieve a breakthrough in the development of hydrogen storage materials by discovering the class of reversible intermetallic hydrides. In 1958 they discovered that the intermetallic compound ZrNi reacts reversibly with gaseous hydrogen to form the ternary hydride ZrNiH 3 .…”
Section: Conventional Metal Hydridesmentioning
confidence: 99%
“…The existence of the two intermediate phases, NiZr2 and NiZr, was first reported by Hayes, Roberson & Paasche (1953); however, they were unable to identify the structures of either of these phases from polycrystalline diffraction data. Libowitz, Hayes & Gibb (1958) studied the system NiZr-H and found that the phases NiZr, NiZrH and NiZrH8 gave similar diffraction patterns which were tentatively indexed on the basis of a distorted cubic cell with lattice parameter varying between 6.98 A and 7-40 A. The results of the present investigation do not corroborate the tentative indexing, but rather indicate that the phase NiZr has the orthorhombic By type structure (Structure Reports, 12, p. 30, 1949) typified by ~-CrB as reported by Kiessling (1949).…”
Section: Introductionmentioning
confidence: 99%
“…That year, Libowitz et al observed that at a given temperature ZrNiH 3 has a desorption pressure much higher than the one measured for ZrH 2 . Thus, ZrNiH 3 has an enthalpy of decomposition lower than that of ZrH 2 [131]. Similarly, in 1967, Reilly et al [132] reported on the possibility to change the reaction enthalpy of a hydride by mixing it with compounds with a proper stoichiometric ratio, which reversibly react with the hydride during desorption to form a stable compound.…”
Section: Tailoring the Hydrogen Storage Properties Of Tetrahydroboratesmentioning
confidence: 99%
“…Several strategies have been applied to tailor the thermodynamic and kinetic features of the above mentioned borohydrides, aiming to reach the targets set by U.S. Department of Energy DoE [125]. The most relevant strategies are: (1) addition of catalytic additives [126][127][128][129][130]; (2) thermodynamic tuning via hydrides mixtures [131][132][133][134][135]; and, (3) nanoconfinement of tetrahydroborates and their hydride mixtures [95,[132][133][134][135][136][137][138].…”
Section: Tailoring the Hydrogen Storage Properties Of Tetrahydroboratesmentioning
confidence: 99%